Price-cost margin in the pharmaceutical industry: Empirical evidence from Finland - Ismo Linnosmaa; Raine Hermans; Taru Karhunen (The Research Institute of the Finnish Economy (ETLA), 2002)
Aim of this paper is to estimate price-cost margin in the Finnish pharmaceutical industry. The estimation is based on the method developed by Hall (1988), who shows that, under constant returns to scale, the total factor productivity depends on the growth rate of output-capital ratio if the market is imperfectly competitive. The measurement of price-cost margin is based on this theoretical result. We utilize data on the Finnish pharmaceutical industry. The data covers the years 1975-1999 and includes information on output, labor hours and capital stock both in nominal and real terms. According to the results, the estimated price-cost margin is in the range 0.59 - 0.67, which is close to the estimates obtained in the US markets. – Pharmaceuticals ; pricing ; competition ; regulation
Keywords: 330; Betriebliche Preispolitik; Pharmazeutische Industrie; Arzneimittelmarkt; Finnland